2010
DOI: 10.2353/ajpath.2010.090009
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Lesion Progression Changes Lysophosphatidic Acid Homeostasis to Favor its Accumulation

Abstract: Lysophosphatidic acid (LPA) accumulates in the central atheroma of human atherosclerotic plaques and is the primary platelet-activating lipid constituent of plaques. Here, we investigated the enzymatic regulation of LPA homeostasis in atherosclerotic lesions at various stages of disease progression. Atherosclerotic lesions were induced in carotid arteries of low-density lipoprotein receptor-deficient mice by semiconstrictive collar placement. At 2-week intervals after collar placement, lipids and RNA were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 44 publications
7
57
0
Order By: Relevance
“…We and others have previously demonstrated that LPA progressively accumulates in plaques during disease progression ( 20,21 ) and we here confi rmed the presence and actual location of a range of LPA species in the atherosclerotic Fig. 3.…”
Section: Local Lpa Treatment and Plaque Morphologysupporting
confidence: 54%
See 3 more Smart Citations
“…We and others have previously demonstrated that LPA progressively accumulates in plaques during disease progression ( 20,21 ) and we here confi rmed the presence and actual location of a range of LPA species in the atherosclerotic Fig. 3.…”
Section: Local Lpa Treatment and Plaque Morphologysupporting
confidence: 54%
“…During the development of atherosclerosis, tissue concentrations of LPA increase ( 21 ), thus enhancing local bioavailability of LPA with the capacity to destabilize plaques. Apoptosis at later stages of disease progression is considered deleterious for plaque stability ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In basic studies, for example, LysoPA causes the migration of smooth muscle cells and activated platelets, while S1P increases the integrity of blood vessels, protects epithelial cells and macrophages from apoptosis and induces eNOS in epithelial cells. In clinical studies, LysoPA has been found to be abundant in the lipid core region of human atherosclerotic plaques 6,7) . Additionally, the plasma LysoPA levels are higher in patients with acute coronary syndrome 8) , whereas the plasma S1P levels and HDL-linked S1P levels are lower in those with ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%